2018
DOI: 10.3390/pathogens7040077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specific Electric Field Stimulation on the Release and Activity of Secreted Acid Phosphatases from Leishmania tarentolae and Implications for Therapy

Abstract: Leishmaniasis is a neglected tropical disease with 1.6 million new cases reported each year. However, there are few safe, effective, and affordable treatments provided to those affected by this disease. Still under-appreciated as potential pharmaceutical targets, especially for cutaneous leishmaniasis infections, are the two isozymes of secreted acid phosphatase (SAP). These enzymes are involved in the survival of the parasite in the sand fly vector, and in infecting host macrophages. While the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We have previously reported that Leishmania tarentolae are able to synthesize nitric oxide [ 15 ]. This is especially of interest since there are reports that both nitric oxide production and secreted acid phosphatase are linked to successful parasite-host interactions [ 15 , 16 ]. We can thus speculate that a modest decrease in parasite virulence is likely in regions richer in strontium and perhaps bismuth.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that Leishmania tarentolae are able to synthesize nitric oxide [ 15 ]. This is especially of interest since there are reports that both nitric oxide production and secreted acid phosphatase are linked to successful parasite-host interactions [ 15 , 16 ]. We can thus speculate that a modest decrease in parasite virulence is likely in regions richer in strontium and perhaps bismuth.…”
Section: Discussionmentioning
confidence: 99%
“…SAP Enzyme Kinetic Assay using Selected Test Compounds (following the method of Dorsey et al . [ 28 ]): A stock culture of L. tarentolae in the late stationary phase, was pelleted, retaining the supernatant. This standard pool of SAP enzyme was separated into equal volumes and allowed to incubate with 30 µM compounds 6 , 1c , and 1e .…”
Section: Methodsmentioning
confidence: 99%
“…This strain of Leishmania is generally regarded as non-pathogenic to humans, and it therefore serves as a model system in vitro [ 26 ]. We observed that these compounds negatively affect parasite growth and viability in vitro with mechanistic targets such as nitric oxide production and secreted acid phosphatase activity, both of which are proposed to be involved in parasite-host interactions [ 27 , 28 ]. We also included tests against mammalian glial cells, in culture, to evaluate toxicity for another cell type.…”
Section: Introductionmentioning
confidence: 99%
“…In leishmaniasis, the use of therapeutic electricity applied on infected mice with L. major showed important death of parasites at the lesion sites [91]. Recent advances have demonstrated that electric fields affected leishmania tarentolae promastigote motility, clumping and viability in vitro [92]. However, these studies are in an initial phase requiring more data related to what currents, potentials, numbers of stimulations, and durations are safe but effective for clinical use against CL.…”
Section: Electrotherapymentioning
confidence: 99%